Investigation into Physical and Pathophysiological Changes of Hemodynamics on Segmented Patient-Specific Cerebral Aneurysm Models through Computational Analysis - Lim, Sheh Hong; Mohd Azrul Hisham, Mohd Adib; Mohd Shafie, Abdullah; Nur Hartini, Mohd Taib; Radhiana, Hassan; Azian, Abd Aziz (IEEE, 2021)
Growth and rupture of human cerebral aneurysm are risky as both of these stages may lead to human organ dysfunction arisen from neurological disorders. The rupture of cerebral aneurysm can even lead to fatal hemorrhaging and other serious health issues. Several sets of medical images from patients have been utilized to reconstruct patient-specific cerebral aneurysm model geometries with different threshold value through image segmentation for computational analysis. In this paper, the physical and pathophysiological changes on hemodynamics, namely geometry volume, inlet area, outlet area, wall shear stress (WSS) distribution, and velocity flow field in the particular models are discussed. A prediction on the location where the aneurysm grows and ruptures has been made. Besides, the model geometries have been validated with varied mesh size. The simulation results show that the mesh size which is applied on the model geometry has significant effect on the generated WSS and velocity values, when varying within certain range. From the findings, the mesh size is one of the important elements which should be optimized, other than the threshold value used for model geometry reconstruction.